Religious Associations in Tatar Assr under Conditions of Mass Political Repressions of the 1930 - Ibragimov, Ruslan Rustamovich; Fazliev, Aivaz Minnegosmanovich; Samatova, Chulpan Khamitovna (Cuestiones Políticas, 2020)
The paper discusses the situation of confessional associations in the Autonomous Soviet Socialist Republic of Tatar during the period of mass political repressions de in the late 1930s. The methodological basis was the civilizational approach, as well as the principles of objectivity, historicism, and social focus, which allowed the most effective development of the issue raised. The specificity of the period and the object of study are determined by the heyday of Stalinist repression and religious consciousness, which was carried by believers and clergy, and was not correlate with communist ideology. The very fact of the existence of the aforementioned believers and the clergy and the presence of Orthodox churches, mosques, Catholic churches and functioning religious buildings of other religions was fundamentally in line with the goals and objectives that the state authorities established during this period. By way of conclusion, the authors provide detailed statistical information (in support of their scientific arguments and conclusions) on the dynamics of the number of prayer buildings in the republic during the study period and at the same time account of the general conditions of mass repression that characterize the historical context.